8: IMPACT OF LATE USE MAGNESIUM SULFATE IN INNER CITY CHILDREN HOSPITALIZED FOR ASTHMA EXACERBATION. Issue 3 (23rd February 2016) - Shukla, P; Aragona, E; Wang, J; Pillai, D
Abstract : Purpose of Study: Asthma is typically treated acutely with β2-agonists and systemic steroids. Adjunctive therapies such as magnesium sulfate (MgSO4 ) have proven useful with early addition potentially improving clinical outcomes in asthma (reduced hospital admission rates, length of stay and intubation rates). Exact administration time and impact on outcomes in children are not fully understood. We sought to identify the impact of timing of initiating MgSO4 therapy in innercity children admitted for status asthmaticus. Methods Used: We performed a retrospective chart review of children (age 2–21 yrs) admitted to a children's hospital over a 12 month period with asthma exacerbation and administered MgSO4 . Data collected included ethnicity, gender, medications, timing of interventions, length of stay, BMI percentile, comorbidities and NAEPP asthma severity. Statistical analysis performed with SPSS 22. Summary of Results: 150 innercity children were admitted for asthma exacerbation and received MgSO4 during the study period. 85% were African American, 36% female, 39% had moderate/severe asthma and mean time to initial MgSO4 was 3.8 hours from triage. Those receiving initial MgSO4 after 4 hours were more likely to receive multiple doses of MgSO4 (OR2.8 [95%CI:1.4–5.6]). Time of initial MgSO4 dose (<4 vs. >4 hrs) showed no significant difference in other parameters including age, obesity, asthma severity, and comorbidities. A sub-analysis of children that received 1 dose vs. >1 MgSO4 dose demonstrated that those receiving >1 MgSO4 doses were more likely to be obese (OR2.7 [1.3–5.7]), have moderate/severe asthma (OR3.2 [1.6–6.8]) and have increased length of stay (p=0.005) and charges (p=0.042). Additionally, obese children (OR8.9 [2.2–35.2]), and intermittent/mild asthmatic children (OR6.4 [1.2–31.2]) receiving >1 MgSO4 dose were more likely to have >2 day length of stay. Conclusions: Delay in administration of MgSO4 in children hospitalized for status asthmaticus may be associated with poor outcomes including multiple doses of MgSO4 which in turn is associated with longer length of stay and increased charges. Obesity and asthma severity are important factors associated with these outcomes. A prospective analysis in a larger cohort is recommended to further evaluate these findings.